ACTIVITIES OF FERGANA REGION EYE DISEASES HOSPITAL - Rukhiddin Kh. Patkhiddinov (International Scientific and Current Research Conferences, 2023)
This article describes the state of treatment of eye diseases during the colonial period of the Russian Empire and the establishment and operation of the hospital for eye diseases in New Margilon.